The difference between the control and the experimental groups of students in vocabulary learning strategies - Mohd Nazri, Latiff Azmi; Husam Ibrahim, Mohammad Alqudah (2019)
Vocabulary learning strategies enhance reading comprehension, which is considered as an essential part of English language learning as without grammar, very little can be conveyed; Without vocabulary, nothing can be conveyed. The literature of vocabulary learning has highlighted the importance of using vocabulary learning strategies as they help students in their English Learning process. However, few studies have been conducted to offer more insights into the vocabulary learning strategies (VLS) used by EFL learners. Hence, the researchers are concentrating on understanding the process of learning vocabulary, making students self-sufficient in learning. Therefore, the present study investigates the role of VLS in reading comprehension.